Control of Ribosome Synthesis in Escherichia coli: Analysis of an Energy Source Shift-Down - Molin, Søren (1977)
The rate of ribosome synthesis and accumulation in Escherichia coli during the transition after an energy source shift-down was analyzed. The shift was imposed on cultures of stringent and relaxed strains growing in glucose minimal medium by the addition of the glucose analogue α-methylglucoside. In the stringent strain, ribosome synthesis was almost instantaneously reduced after the shift, whereas the relaxed strain exhibited a more gradual response. The rate of messenger ribonucleic acid (mRNA) synthesis was affected similarly, though to a smaller extent. A comparison of the rates of synthesis and accumulation of ribosomal RNA (rRNA) and ribosomal proteins showed that far more ribosomal components were synthesized after the shift than were accumulated, indicating that a substantial part of the rRNA made after the shift was unstable. A new method was used to measure relative rates of rRNA synthesis and to estimate the transcription time for the rRNA operon under different conditions. In steady states of growth with growth rates ranging from 0.75 to 2.3 doublings/h, as well as during the transition after a shift-down, the transcription time of the rRNA operon was constant. The rate of synthesis of rRNA correlated during this transition – in contrast to the rate of accumulation (M. T. Hansen et al., J. Bacteriol. 122: 585-591, 1975) – with the ppGpp pool in the same way as has been observed during partial amino acid starvation.